Il bene e il suo contesto: il monitoraggio termografico e ambientale, metodo integrato per orientare strategie di conservazione e verificarne l'efficacia - Monica Volinia; Mario Girotto (Restauro Archeologico)
Long-term monitoring of the Chapel of Sant'Eldrado at Novalesa Abbey has been crucial in developing integrated analytical methods to support conservation strategies. The research, since 2012 assessed the preservation of the chapel's frescoes. Thermographic and environmental monitoring have underlined the importance of thermal fluctuations on the walls, rather than water infiltration or condensation, as the primary cause of decay. These findings led to the development of corrective actions to mitigate environmental factors contributing to the deterioration, including installing a natural heat shield that stabilized the temperature on the affected walls. This integrated approach proved essential for tracking, addressing, and preventing the ongoing degradation and emphasized the importance of continuous monitoring. It also highlighted the value of collaboration between professionals and institutions to ensure the long-term protection and preservation of the chapel's historical and artistic heritage.